Diagnostic Accuracy of MRI in Diagnosing Malignant Adnexal Masses, taking Histopathology as the Gold Standard - Abbas, Samia; Nisar, Sarah; Naseem, Kamran; Samad, Maryam (Indus Journal of Bioscience Research, 2025)
Objective: This study aims to evaluate the diagnostic accuracy of Magnetic Resonance Imaging (MRI) in identifying complicated adnexal masses, using histopathology as the reference standard. Methods: Conducted at the Department of Radiology, Bahawal Victoria Hospital in Bahawalpur, between March 2024 and September 2024, this cross-sectional study involved performing both MRI and histopathological evaluations on patients with adnexal masses. The histopathology results served as the gold standard for comparison with MRI findings. Data analysis was performed using SPSS version 20. Results: The study participants had an average age of 31.2 ± 15.5 years. MRI demonstrated a sensitivity of 97.1% and a specificity of 87.2% in diagnosing complicated adnexal masses. Conclusion: Contrast-Enhanced MRI is a highly reliable and accurate diagnostic tool for evaluating complicated adnexal masses. Its high sensitivity and specificity make it a valuable complement to histopathology in the diagnostic process.